Binding Sources of International Law vis-à-vis Uṣūl al-fiqh: Towards Developing the Turath on Fiqh al-Siyar - Fajri Matahati Muhammadin (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
Some contemporary Islamic scholars often merely regurgitate classical scholarship of fiqh al-siyar (Islamic international law) while oblivious of major shifts in the world order back then versus today. Other contemporary scholars do the opposite mistake: going straight to the Qur’an and Sunnah, ignoring over a millennium worth of turath (Islamic scholarly tradition) and end up cherry-picking verses to support inferiority-complex-infused versions of Islam and subjugated by Eurocentric notions of international law. Hence, fiqh al-siyar is currently in a state of lethargy in turath requiring major projects for development. My research will touch uṣūl al-fiqh (jurisprudence) specifically regarding the sources of Islamic law and how, from them, ijtihad is conducted when interacting with contemporary international law. This is among the foundational issues upon which many further developments of fiqh al-siyar need to be established. I apply Al-Attas’s “Islamization of Contemporary Knowledge” approach to comprehensively analyze the sources of international law to consider how Islamic law should react and respond to them. For this project, I focus on formally binding sources of international law (treaties, customary international law, general principles of law, and jus cogens). My two findings: (a) most of these sources should not be categorically accepted or rejected (must be carefully considered case-per-case), and (b) jus cogens, in terms of legal status, should be categorically rejected.